METHODS OF DIFFERENTIATION OF ECOLOGICAL AND GEOMORPHOLOGICAL SYSTEMS OF DENUDATION PLAINS OF ARID ZONE (CENTRAL KAZAKHSTAN) (Journal of Geography and Environmental Management, 2025)
The article deals with the problem related to the insufficient attention paid to the issue of ecological and geomorphological zoning of platform plains of arid zones in the economic use of their potential. Possibilities and scales of use of territorial taxa of such zoning depend on the principles underlying their allocation and are one of the important applied tasks of effective land use. The importance of these tasks is especially great for arid and semi-arid territories of the platform-denudation plains of Kazakhstan. Errors in land use can lead to irreversible degradation of natural systems in conditions of moisture deficit, which is a ‘cushion’ of safety of territorial zoning systems. The existing methods of differentiation of geomorphological systems and assessment of their ecological state do not fully meet the requirements of not only rational land use, but also, in general, effective nature management. The authors believe that one of the methods of adequate differentiation of ecological and geomorphological systems is strip profiling, which allows to reveal the geomorphological state of space in a strip from 10 km to 20 km from the main line of the profile at a given, in this study, scale. Strip profiling should be used in conjunction with the methods mentioned in this paper.
Keywords: relief and relief-forming processes; geomorphological system; ecological-geomorphological study; environment; land use; regional development; cartographic method.